Menjadi Gereja yang Ramah: Telaah Kritis Keterlibatan Generasi Z dalam Pelayanan di Gereja - Marchelin Sarubang (CARAKA: Jurnal Teologi Biblika dan Praktika, 2023)
In service, hospitality is needed as a bridge to build good relationships between generations. The lack of involvement of young people in presenting the identity of the Church, which has not been open to the diversity of creativity in today's worship. Generation Z as the largest population in the world now understands and has extensive knowledge about the world that can be reached with the digital world. The church needs generation Z to create new colors in services, especially public worship. It is important for the Church to develop and pay attention to the world of technology, including social media, as a relevant means to enhance engaging services for Generation Z. This paper directs the Church with hospitality to embrace and involve young people to play a role in ministry, especially public worship. This will also help the Church to become aware of and bridge the generational gap, as well as strengthen intergenerational relationships.